1987
DOI: 10.1111/j.1476-5381.1987.tb10283.x
|View full text |Cite
|
Sign up to set email alerts
|

D2‐dopamine receptor‐mediated inhibition of intracellular Ca2+ mobilization and release of acetylcholine from guinea‐pig neostriatal slices

Abstract: 1 The effect of dopamine receptor activation on electrically-or high K+ (30 mM)-evoked neurotransmitter release and rise in intracellular Ca2" concentration was investigated using slices of guinea-pig neostriatum. 6 When the slices were superfused with the Ca2+-free medium containing EGTA (10-M) for 5 min, the rise in [Ca2+i] was markedly suppressed to 18.0% of control by LY-171555 (10-6 M). 7 These data indicate that activation of the D2-dopamine receptor suppresses the elevation of [Ca2+]i induced by depola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1988
1988
1996
1996

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…Presumably, the effects of the DA agonists were reduced in synaptosomes from the reserpine-treated rats, because reserpine in vivo had increased the impulse activity in DA neurons (German et al, 1981), thus increasing the Ca2+ concentration (Baker et al, 1971), and DA autoreceptors may normally control DA synthesis by decreasing the free intraneuronal Ca2+ concentration and, consequently, the Ca2+-dependent phosphorylation of TH. This concept is in line with the report of Fujiwara et al (1987) that electrical stimulation of striatal slices increased the influx and intraneuronal mobilization of Ca2+, and that the D, agonist quinpirole inhibited the mobilization of Ca". Recently, von Euler et al (1992) reported that stimulation of D, receptors with quinpirole decreased the levels of cytosolic free Ca2+ in the human cerebrocortical cell line HCN-1A.…”
Section: Discussionsupporting
confidence: 91%
“…Presumably, the effects of the DA agonists were reduced in synaptosomes from the reserpine-treated rats, because reserpine in vivo had increased the impulse activity in DA neurons (German et al, 1981), thus increasing the Ca2+ concentration (Baker et al, 1971), and DA autoreceptors may normally control DA synthesis by decreasing the free intraneuronal Ca2+ concentration and, consequently, the Ca2+-dependent phosphorylation of TH. This concept is in line with the report of Fujiwara et al (1987) that electrical stimulation of striatal slices increased the influx and intraneuronal mobilization of Ca2+, and that the D, agonist quinpirole inhibited the mobilization of Ca". Recently, von Euler et al (1992) reported that stimulation of D, receptors with quinpirole decreased the levels of cytosolic free Ca2+ in the human cerebrocortical cell line HCN-1A.…”
Section: Discussionsupporting
confidence: 91%
“…Activation of the D2-dopamine receptor inhibits acetylcholine release via its inhibition of intracellular Ca2+ mobilization in guinea pig neostnatal slices (Fujiwara et al, 1987). Provided that the D2-dopamine receptor is coupled to the inhibitory GTP-binding pro-tein, its inhibitory action on acetylcholine release and intracellular Ca2+ mobilization may be mediated by decreased levels of intracellular cyclic AMP, which suggests that enhancement of the evoked release induced by elevation of intracellular cyclic AMP levels may be due to an increase of intracellular Ca2+ mobilization.…”
Section: Discussionmentioning
confidence: 98%
“…The anticholinergic effects of dopamine are mediated by dopamine D2 receptors (Hoffman et al, 1986;Stoofet al, 1982Stoofet al, , 1987Fujiwara et al, 1987). For the full syndrome of motor activation, D t receptor stimulation is also required (Robertson andRobertson.…”
Section: Towards a More Complete Model Of The Striatummentioning
confidence: 95%
“…Dopamine agonists depress the acetylcholine turnover rate and the enzymatic activity of choline acetyltransferase (Bluth et al, 1985). In particular, D2 dopamine ag-onists inhibit acetylcholine release (Stoof et al, 1982(Stoof et al, , 1987Hoffman et al, 1986;Fujiwara et al, 1987). DiFiglia (1987) found that intrinsic cholinergic boutons sometimes converged onto the same dendritic spines as corticostriatal afferent axons.…”
Section: Dopamine and Acetylcholinementioning
confidence: 98%